HEMATOPOIESIS RESTORATION AFTER AUTOLOGOUS BONE MARROW TRANSPLANTATION USING A FROZEN GRAFT - Achilova, O.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The springboard for hematopoiesis is the bone marrow located in the spongy bones. Hematopoiesis assessment is primarily carried out by assessing the ratio of hematopoietic, adipose and bone tissue. The ratio in the study is 1:0.8:0.5 as the norm. A hematopoietic area of less than one was assessed as a hypocellular biopsy. In 40 patients who underwent autologous bone marrow transplantation with cryo-frozen stem cells, 20 trepanobiopsies were examined within +30 days after autologous bone marrow transplantation. Ten trepanobiopsies were performed on patients with lymphomas and 10 on patients with myeloma.